Circular RNA and intervertebral disc degeneration: unravelling mechanisms and implications - Xie, Guohao; Wu, Tingrui; Ji, Guangju; Wu, Hang; Lai, Yue; Wei, Bo; Huang, Wenhua (Frontiers in Molecular Biosciences, 2023)
Low back pain (LBP) is a major public health problem worldwide and a significant health and economic burden. Intervertebral disc degeneration (IDD) is the reason for LBP. However, we have not identified effective therapeutic strategies to address this challenge. With accumulating knowledge on the role of circular RNAs in the pathogenesis of IDD, we realised that circular RNAs (circRNAs) may have tremendous therapeutic potential and clinical application prospects in this field. This review presents an overview of the current understanding of characteristics, classification, biogenesis, and function of circRNAs and summarises the protective and detrimental circRNAs involved in the intervertebral disc that have been studied thus far. This review is aimed to help researchers better understand the regulatory role of circRNAs in the progression of IDD, reveal their clinical therapeutic potential, and provide a theoretical basis for the prevention and targeted treatment of IDD.